2018
DOI: 10.1002/mpr.1741
|View full text |Cite
|
Sign up to set email alerts
|

Measurement invariance of the Spanish Launay–Slade Hallucinations Scale‐Extended version between putatively healthy controls and people diagnosed with a mental disorder

Abstract: Objectives The current study aimed at evaluating the reliability, convergent and divergent validity, and factor structure of the Spanish Launay–Slade Hallucinations Scale‐Extended version (LSHS‐E) in people with mental disorders and healthy controls. Methods Four hundred and twenty‐two individuals completed the Spanish LSHS‐E and the Spanish Community Assessment of Psychic Experiences. The convergent and divergent validity of the LSHS‐E was assessed with the three dimensions of the Community Assessment of Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 60 publications
(90 reference statements)
7
32
3
Order By: Relevance
“…6,9,16,18–22 However, structures often differed depending on the version of the LSHS used in each study. This study replicated the 4-factor structure of the LSHS-E as reported by previous studies,13,20,21 providing some consistency for 4-factors of the propensity to experience HLEs in the general population. Moreover, this version fully matches the factor-structure reported by Larøi 9 in one of the original studies.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…6,9,16,18–22 However, structures often differed depending on the version of the LSHS used in each study. This study replicated the 4-factor structure of the LSHS-E as reported by previous studies,13,20,21 providing some consistency for 4-factors of the propensity to experience HLEs in the general population. Moreover, this version fully matches the factor-structure reported by Larøi 9 in one of the original studies.…”
Section: Discussionsupporting
confidence: 87%
“…However, depending on the response format used and the number of items included in the scale, different factorial structures were found. These structures included 2-factor, 10,15 3-factor, 6,17–19 4-factor, 9,13,20–22 and 5-factor 16 models. Furthermore, despite the globalization of research on the factor structure of the LSHS-Extended (LSHS-E), no study to date has explored the measurement invariance of this tool across countries and clinical status.…”
Section: Introductionmentioning
confidence: 99%
“…Our results did not conflict with the findings of Siddi et al ( 34 ), as the Launay–Slade Hallucinations Scale-Extended version does not include a non-specific item corresponding to PQ-B item 12, or an item that can be interpreted as body dysmorphia.…”
Section: Discussioncontrasting
confidence: 52%
“…Since items with this kind of content partially depend on depression levels, they should be considered for exclusion when the intention is to measure PLEs specifically, rather than, for example, screening for psychosis risk, where depression is a relevant risk factor of its own, and conceptual disentanglement is less critical. Our results did not conflict with the findings of Siddi et al (34), as the Launay-Slade Hallucinations Scale-Extended version does not include a non-specific item corresponding to PQ-B item 12, or an item that can be interpreted as body dysmorphia.…”
Section: Depressioncontrasting
confidence: 57%
See 1 more Smart Citation